ChemInform Abstract: Rhodium‐Catalyzed Tandem Annulation and [5 + 1] Cycloaddition: 3‐Hydroxy‐1, 4‐enyne as the 5‐Carbon Component. Issue 22 (3rd June 2014) - Li, Xiaoxun; Song, Wangze; Tang, Weiping
Abstract A variety of substituted carbazoles and dibenzofuran (XIV) are efficiently prepared via a Rh‐catalyzed tandem annulation/[5 + 1]‐cycloaddition sequence using 3‐hydroxy‐1, 4‐enynes as a new 5‐carbon component in the cycloaddition step.